Microwave Extraction of Essential Oils from ‘Penaga Lilin’ (Mesua Ferrea L.) Leaves - Nurdin, Rudy (2007)
The purpose of this research is to compare the performance of the Microwave Extraction Technique (MET) with the Conventional Extraction Technique (CET) in extracting an essential oils from Mesua ferrea L. leaves using various methods such as dry distillation (DD), wet distillation (WD), hydro distillation (HD) and steam distillation (SD) in terms of its rapidity and efficiency to extract the quality percentage of yield and chemical composition of essential oil. The important extraction process parameters, i.e, time, temperature and microwave power output are controlled to obtain the highest quantity and quality of essential oil rapidly. The MET is performed using DD and WD at irradiation power of about 450 W and temperature about 100oC for 1 hour whereas CET is performed using HD and SD at extraction power of 450 W and temperature 100oC for 8 hours. The absorption power of microwave irradiation by Mesua ferrea L. leaves are also estimate for DD and WD. This is to determine which method gives higher value of absorption power. By estimating the absorption power in order to know which method is more efficient in heating process. The MET provides a rapid extraction, with about 8 times faster than CET. After 1 hour of MET, it is possible to collect sufficient essential oil which provides comparable yields to those obtained 8 hours using CET. From 200 g actual weight of leaves, during HD gives the highest yield of extracted essential oil with 0.057% of weight compared to WD with 0.039% whereas DD gives 0.031% and SD which provides the least yield contributes 0.021%. Although more compounds are detected in the essential oil extracted by CET, substantial higher amounts of highly odoriferous compounds are present in the MET extract. During MET, DD requires only 5 minutes to obtain its first essential oil droplet and WD requires 19 minutes whereas during CET, both HD and SD requires 27 and 36 minutes, respectively. DD requires less time to obtain its first oil droplet compared to the other methods due to higher absorption power for dry sample than for wet sample. It is found that the absorption power in DD is 3 times higher with W/m3 compared to WD with only W/m3. This is due to higher electric field strength inside the dry sample with V/m compared to the wet sample with V/m. This shows that MET is 70% more efficient in heating proses compared to CET only 50%. In terms of the power output consumed for 1 hour of MET and 8 hours of CET, DD requires the least energy with 12 kW whereas WD requires 17 kW while both HD and SD consume higher energy 216 kW. This shows that energy can be saved about 13 to 18 times using MET. In terms of the economical aspect, the MET is cost saving compared to CET. The rate of cost energy consumption for the extraction cost during MET for both DD and WD performed for 8 hours are RM 3.71 and RM 5.23, respectively whereas during CET, both HD and SD involve an extraction cost of RM 11.77, respectively. This shows that about RM 6.54 to RM 8.06 can be saved by using MET. The project successfully proved the MET is an alternative technique for the extraction of essential oils from plant materials like leaves. Essentially, the MET provides an easily controlled system, rapid and safe extraction process; high yield and purity extracts, more valuable and good quality of essential oils, extracts with chemical compositions comparable to conventional method and allows a substantial saving of energy. These advantages not only reduce operating costs, but also result in a more environmental friendly extraction process.